Studies on Current Health and Safety Practices and Their Impact on Accidents on Nigerian Construction Sites - Muhammad Muktar; Ezekiel Chinyio (Advanced Aspects of Engineering Research Vol. 8, 2021)
Accidents on construction sites in Nigeria have caused and still cause devastating effects on properties and the lives of workers, as well as affecting the delivery of projects on time and within budget. However, little has been done to address this critical issue. Several hundreds of construction workers are killed each year on Nigerian construction sites, with many more rendered temporarily or permanently disabled. A study was thus carried out on the perceptions of professionals on the current health and safety (H&S) practices on Nigerian construction sites. A quantitative method was used where a survey questionnaire was administered to potential respondents. One hundred and fifty questionnaires were administered and 100 responses were ultimately collected, representing a response rate of 66.6%. The data were analysed by descriptive and inferential statistics to reveal that poor H&S practices are evident on Nigerian construction sites, particularly: the lack of commitment to safety by stakeholders, lack of governmental support, little or no diligence while enforcing safety regulations on site and lack of safety education programmes on site. Also, accidents can be attributed to many sources, chiefly non-compliance with safety regulations, carelessness of workers, weak coordination of workers on site and ineffective safety culture. The safety performance of many projects in Nigeria is still below par. As the causes of accidents in Nigerian construction are many, likewise efforts by many stakeholders are needed to address the issue. Government, professional bodies and contractors can play leading roles in bringing improvements.